2015
DOI: 10.1021/ef502815x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Commercial Anti-agglomerants and Ammonium Quaternary Compounds on the Stability of Waxy Crude Oil Emulsion

Abstract: Understanding the anti-agglomerant (AA) contributions to the physicochemical properties of waxy petroleum emulsions can provide improvements on handling problems caused by hydrates during petroleum production. This work evaluated the stability of a reference water-in-oil (W/O) emulsion perturbed by the presence of commercial hydrate AAs and ammonium quaternary compounds. The results showed that emulsion mean droplet size was not sensitive to the presence of these chemicals. Both W/O emulsions, with and without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Free of this subfraction, the interface becomes thin and less rigid, without any noticeable aging effect (increased stiffness over time). The chemical analysis of this subfraction showed that oxygen composition is higher than the oxygen composition of the complete asphaltene sample 2015). The presence of solid inorganic fines at interface, such as silica, clays, and metal oxides also contribute for emulsion stabilization (Mehta et al, 2004;Sullivan & Kilpatrick, 2002).…”
Section: Stability and Breaking Of W/o Petroleum Emulsionsmentioning
confidence: 91%
“…Free of this subfraction, the interface becomes thin and less rigid, without any noticeable aging effect (increased stiffness over time). The chemical analysis of this subfraction showed that oxygen composition is higher than the oxygen composition of the complete asphaltene sample 2015). The presence of solid inorganic fines at interface, such as silica, clays, and metal oxides also contribute for emulsion stabilization (Mehta et al, 2004;Sullivan & Kilpatrick, 2002).…”
Section: Stability and Breaking Of W/o Petroleum Emulsionsmentioning
confidence: 91%
“…Protonated amines (R 3 NH + ) and carboxylic acids (R-COOH) have also been described as the most reactive organic species towards negatively-charged groups on the reservoir rock surface 37 ; but in comparison with R-COOH, the R 3 NH + functionality is underexplored in the field of low-salinity EOR. The functionality, investigated in this work, is the simplest representation of often more complex nitrogen-containing organic compounds present in crude oil 36 , and of some amine-based surfactants 38 , 39 which might be present in the reservoir from secondary surfactant floods, or indeed, could be present in the water flood for low-salinity-surfactant EOR. To probe the impact of the ion type—specifically Ca 2+ in comparison with other aqueous electrolytes on the influence of concentration—all aqueous electrolytes were used at the same two concentrations, 0.1 M and 0.3 M, which were accessible by both simulation and experiment; 0.1 M is at the lower limit of what could be reliably modeled using atomistic MD simulations.…”
Section: Introductionmentioning
confidence: 99%